Fitness on Grape Berries of Botrytis cinerea Isolates Belonging to Different Dicarboximide Sensitivity Classes - Fourie, P.H.; Holz, G. (South African Journal of Enology and Viticulture, 2017)
Seasonal fluctuations in the frequency of dicarboximide-resistant Botrytis cinerea isolates in Western Cape vineyards suggest a reduced fitness of these isolates. In this study fitness of sensitive, ultra-low-level and low-level dicarboximide-resistant isolates of B. cinerea were compared on grape berries. Conidia were dispersed as single cells on berry surfaces from airborne inoculum in a settling tower or deposited as clusters in water droplets. Investigations were conducted at two potential infection courts on dicarboximide treated and untreated berries, namely the intact cuticle and wounds. Surface sterilisation, isolation and freezing techniques were used to determine surface colonisation and penetration by airborne inoculum. Decay incidence, severity and sporulation incidence were determined following inoculation with conidial clusters. The different tests indicated that germlings of dicarboximide-sensitive and -resistant isolates had similar surface-colonising abilities of dicarboximide-free berries. However, sensitive strains penetrated significantly more often. Fitness decreased with an increase in the level of dicarboximide resistance. Iprodione caused a drastic disturbance in the ratio of different dicarboximide sensitivity classes that occupied the berry surface and allowed the development of germlings of predominantly resistant isolates, but with few successful infections. Significantly higher levels of infection and proliferation of dicarboximide-resistant isolates on sprayed or unsprayed berries were facilitated by wounding or the termination of host resistance (freezing). According to these findings, these modes of infection should not contribute to a gradual build-up of inoculum of either dicarboximide-sensitive or -resistant isolates. Trends by airborne conidia described here suggest that another primary infection event in the vineyard, most likely floral infection and subsequent debris colonisation, should largely regulate the dynamics between dicarboximide-sensitive and -resistant isolates in B. cinerea populations on grapevine.